The way of attracting foreign investment (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Attracting foreign investment requires a clear and coordinated strategy that focuses on creating an attractive business environment, offering incentives, developing a skilled workforce, investing in infrastructure, and building strong international relationships.